2014
DOI: 10.1017/s0030605312001287
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and protection of the Vulnerable Bengal slow loris Nycticebus bengalensis in Assam and Arunachal Pradesh, north-east India

Abstract: The Bengal slow loris Nycticebus bengalensis is the only strepsirrhine primate in north-east India. It is categorized as Vulnerable on the IUCN Red List. The limited information on its status and ecology is the main hindrance to developing a conservation strategy for this species in India. Therefore during February 2009–May 2010 we surveyed the species in 16 protected areas in Assam and one protected area in Arunachal Pradesh. We used recce transects to estimate encounter rates for the species. A team of 3–4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Rhesus and pig-tailed macaques were only recorded to have died from road accidents because these two species frequently use the ground for movement (Southwick et al 1976, Bernstein 1967. Road accidents are considered as one of the major threats for Bengal slow loris as well (Choudhury 1992, Radhakrishna et al 2006, Kumar and Devi 2010, Das et al 2015. Only Radhakrishna et al (2010) reported an incident of mortality from electrocution in this species near Siju Wildlife Sanctuary in Garo Hills, north- eastern India.…”
Section: Mortality Of Primates Due To Roads and Power Lines In Two Fomentioning
confidence: 99%
“…Rhesus and pig-tailed macaques were only recorded to have died from road accidents because these two species frequently use the ground for movement (Southwick et al 1976, Bernstein 1967. Road accidents are considered as one of the major threats for Bengal slow loris as well (Choudhury 1992, Radhakrishna et al 2006, Kumar and Devi 2010, Das et al 2015. Only Radhakrishna et al (2010) reported an incident of mortality from electrocution in this species near Siju Wildlife Sanctuary in Garo Hills, north- eastern India.…”
Section: Mortality Of Primates Due To Roads and Power Lines In Two Fomentioning
confidence: 99%